Media Rakyat sebagai Media Komunikasi Pembangunan Masyarakat Suku Boti - Petrus Ana Andung; Hotlif Arkilaus Nope (FISIP Universitas Atma Jaya Yogyakarta, 2017)
The Boti tribe in NTT Province prefers to use bonet as a traditional media to deliver development messages. This paper aims to describe the communication pattern as well as meaning construction of bonet as a traditional media of Boti community. This study is a qualitative research using in-depth interviews and participant observation techniques. The results show that bonet is a traditional media, where there is dialogical communication among participants. The Boti people consider bonet as sacred ceremony. Decisions in bonet are considered as a representation of people’s decision. Bonet for the Boti tribe has religious, kinship/friendship, and reconciliation meanings.